2020
DOI: 10.7150/thno.45261
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 promotes tumor progression by increased M2 macrophage infiltration in esophageal squamous cell carcinoma

Abstract: Objective: The transcription factor forkhead box protein O1 (FOXO1) is critical for regulating cytokine and chemokine secretion. However, its function in the tumor microenvironment (TME) remains largely unexplored. In this study, we characterized the prognostic value of FOXO1 and the interaction between tumor-derived FOXO1 and M2 macrophages in esophageal squamous cell carcinoma (ESCC). Methods: FOXO1 expression and macrophage infiltration in clinical samples and mouse models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 35 publications
3
65
0
Order By: Relevance
“…Both CCL20 and its receptor CCR6 are upregulated in skin that has undergone mechanical stretch. CCL20 has been previously reported to regulate macrophage recruitment and facilitate M0 macrophage polarization toward M2 macrophages ( Argyle and Kitamura, 2018 ; Wang et al, 2020c ). Furthermore, our previous study revealed a substantially higher density of M2 macrophages than M1 macrophages during tissue expansion ( Ding et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both CCL20 and its receptor CCR6 are upregulated in skin that has undergone mechanical stretch. CCL20 has been previously reported to regulate macrophage recruitment and facilitate M0 macrophage polarization toward M2 macrophages ( Argyle and Kitamura, 2018 ; Wang et al, 2020c ). Furthermore, our previous study revealed a substantially higher density of M2 macrophages than M1 macrophages during tissue expansion ( Ding et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, fibroblasts in the NPC microenvironment can secrete varied growth factors, including EGF, FGF, IGF1, CSF and TGF-b, which can either facilitate tumor progression or immune suppression (121). For example, CSF-1 is a vital factor inducing M0-to-M2 polarization, TGF-b induces differentiation and activation of Tregs, and IGF-1 is positively correlated to tumor sizes in NPC patients (122,123). Fibroblast growth factor 2 (FGF2) is the upstream molecule of the PI3K/AKT signal pathway and activates proliferation and metastasis of NPC cells so that FGF2/FGFR2 has become a crucial target in the treatment of NPC as well (124).…”
Section: Targeting Fibroblasts To Manipulate the Tumor-promoting Extracellular Matrixmentioning
confidence: 99%
“…Tumor-associated macrophages are the most abundant cancer immune cells. Studies have found that the transcription factor forkhead box protein O1 (FOXO1) can promote the polarization of macrophages M0 to M2 and the recruitment of macrophages M2 in ESCC through transcriptional regulation [74]. Macrophage M2 can be transformed into macrophage M1, and can promote the proliferation, migration and ring-forming ability of lymphatic endothelial cells associated with EC [75].…”
Section: Discussionmentioning
confidence: 99%